Patterns of electoral corruption in Peru: the April 2000 general election - Taylor, Lewis (Crime, law and social change, 2000)
In 2000 Alberto Fujimori became president of Peru for a third consecutive term via an election process of dubious legality. This article details the variety of underhand and fraudulent manoeuvres employed by Peru's ruling clique as its trove to ensure that the regime maintained itself in power. It opens with a review of the thinking behind the government's long-term national development strategy, before outlining its controversial behaviour during the election campaign, irregularities occurring on polling day, as well as when votes were being counted.